A Survey of Moral Concerns and Job-Related Stress among Academic Advisors of College Athletes - Oja, David E. (My University, 1987)
The author surveyed 186 athletic advisors/counselors regarding moral concerns and job-related stress in their jobs with a mailed questionnaire. Within responses, 68.3% noted they occasionally or frequently worry their decisions are based on athlete eligibility over concern for athlete long-term wellbeing, reflecting pressure advisors are under; 82.1% responded occasionally or frequently the advisors are under an uncomfortable amount of stress in their roles; 97.3% of respondents felt they occasionally or frequently made decisions with an ethical or moral consideration.
Keywords: ethics; pressure; stress; burnout; eligibility; well-beiing